2017
DOI: 10.1016/j.socscimed.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of decline in IADL functioning among older survivors following the Great East Japan earthquake: A prospective study

Abstract: Introduction We described associations between the type of disaster experience and change in instrumental activities of daily living among older adult survivors before-after a terrible disaster. Methods The study took advantage of a “natural experiment” afforded by the Japan Gerontological Evaluation Study (JAGES), a nationwide cohort study established in 2010, seven months prior to the earthquake and tsunami. A follow-up survey was conducted in 2013. This study was conducted in Iwanuma, which was directly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Regarding the first explanation, we did not find an association between loss of loved ones and changes in cardiometabolic risk. This lack of long-term associations with health for loss of loved ones is consistent with the existing evidence (24). Moreover, there was no association between changes in Geriatric Depression Scale score and cardiometabolic risk.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the first explanation, we did not find an association between loss of loved ones and changes in cardiometabolic risk. This lack of long-term associations with health for loss of loved ones is consistent with the existing evidence (24). Moreover, there was no association between changes in Geriatric Depression Scale score and cardiometabolic risk.…”
Section: Discussionsupporting
confidence: 89%
“…Older adults are also vulnerable to health problems in the aftermath of disasters. For instance, we have previously reported that older survivors of the 2011 Great East Japan Earthquake experienced increased risks of functional disability, cognitive decline, and depression (18,24,25).…”
mentioning
confidence: 99%
“…These papers focus on post-disaster effects on the physiology and mental health of survivors, including their daily behaviors, physiological indicators, and mental states. [69][70]63 (2) "Public health preparedness." These papers focus on the establishment, evaluation, and management of medical rescue systems.…”
Section: Figurementioning
confidence: 99%
“…As of October 2015, 44,094 people (approximately 2% of the total population in Fukushima Prefecture) were evacuated from Fukushima Prefecture to other prefectures (Fukushima Prefecture 2019). The coastal area of Miyagi Prefecture, located north of Fukushima, was disproportionally affected by the tsunami that struck after the Great East Japan Earthquake, with loss of housing, disruption of access to internal medicine, and adverse effects on daily activities of living (Tsuboya et al 2017). According to previous research, community-level social capital (i.e., bonds of trust between community members, as well as norms of mutual assistance) mitigated the impact of housing damage on cognitive decline (Hikichi et al 2018).…”
Section: Introductionmentioning
confidence: 99%